Pengembangan Bahan Ajar Digital Berbasis Deep Learning Pada Materi Pengelolaan Sumber Daya Alam Di SMA Negeri 1 Kabila - Melani Mokoginta; Sunarty Suly Eraku; M. Iqbal Liayong Pratama (Universitas Negeri Gorontalo, 2026)
Digital technology opens up vast opportunities for developing more innovative and interactive teaching materials. One platform that can be utilized is Google Sites, which allows teachers to systematically organize materials, integrate various learning resources, and present content in multimedia formats such as text, images, videos, and interactive links. In addition to utilizing technology, learning approaches also need to be directed at improving students' in-depth understanding of the material being studied. One relevant approach is the Deep Learning-based approach. This approach emphasizes that the learning process is not merely memorizing information, but rather understanding concepts comprehensively, linking various pieces of knowledge, and being able to apply them in everyday life. Thus, students are expected to be able to develop higher-order thinking skills that are essential in facing global challenges. However, this ideal condition has not been fully realized in learning practices in schools. Based on initial observations at SMA Negeri 1 Kabila, it was found that geography learning is still dominated by conventional methods, such as lectures and the use of textbooks as the primary source. The use of digital teaching materials is still limited, so the learning process tends to be one-way and less engaging for students. This research will be conducted at SMA Negeri 1 Kabila, located in Oluhuta, Kec. Kabila, Bone Bolango Regency. The approach employed by the researchers in this study was research and development (RD). This approach was used because the research focused on product development in the form of deep learning-based digital teaching materials.